Laparoscopic versus Robotic-assisted Rectal Surgery: A Comparison of Postoperative Outcomes. Issue 10 (October 2014) - Young, Monica T.; Menon, Gopal; Feldmann, Timothy F.; Mills, Steven; Carmichael, Joseph; Stamos, Michael J.; Pigazzi, Alessio
Rectal surgery continues to be an area of advancement for minimally invasive techniques. However, there is controversy regarding whether a robotic approach imparts any advantages over established laparoscopic procedures. The aim of this study was to analyze and compare outcomes of laparoscopic and robotic rectal resection operations. A single-institution retrospective review was performed identifying 83 consecutive patients undergoing low rectal resection requiring proximal diversion between 2009 and 2013. The cohort was comprised of 38 laparoscopic and 45 robotic cases. Data were analyzed for postoperative outcomes as well as 30-day morbidity and mortality. Male gender frequency, body mass index, and American Society of Anesthesiologists class were higher in the robotic group (71%, 28.6 kg/m 2, and 2.6, respectively) compared with the laparoscopic group (42%, 23.7 kg/m 2, and 2.2, respectively; P < 0.01). Length of stay was significantly longer for patients undergoing laparoscopic (7.5 days) compared with robotic procedures (5.7 days, P < 0.01). This difference was even greater when comparing patients who underwent a hybrid laparoscopic-assisted open total mesorectal excision (TME) with robotic TME (8.2 vs 5.7 days, respectively, P < 0.01). Conversion rate was 7.9 per cent for the laparoscopic group and zero per cent for the robotic ( P = 0.09). There were no mortalities in either group. A pure laparoscopic or robotic rectal surgery may be associated with a shorter hospital stay compared with a laparoscopic-assisted approach.